Effects of induced sad mood on facial emotion perception in young and older adults. Issue 3 (4th May 2019) - Lawrie, Louisa; Jackson, Margaret C; Phillips, Louise H
ABSTRACT: Older adults perceive less intense negative emotion in facial expressions compared to younger counterparts. Prior research has also demonstrated that mood alters facial emotion perception. Nevertheless, there is little evidence which evaluates the interactive effects of age and mood on emotion perception. This study investigated the effects of sad mood on younger and older adults' perception of emotional and neutral faces. Participants rated the intensity of stimuli while listening to sad music and in silence. Measures of mood were administered. Younger and older participants' rated sad faces as displaying stronger sadness when they experienced sad mood. While younger participants showed no influence of sad mood on happiness ratings of happy faces, older adults rated happy faces as conveying less happiness when they experienced sad mood. This study demonstrates how emotion perception can change when a controlled mood induction procedure is applied to alter mood in young and older participants.